Purple sweet potato innovation as a healthy snack (UMBASA) mini sweet potato with many flavors / Elisa Nurhikmah ... [et al.] - Nurhikmah, Elisa; Dinara, Aliyyah; Devi, Sri; Nurrachmi, Intan (Universiti Teknologi MARA, Kedah, 2024)
In Indonesia, local foodstuffs are very diverse, ranging from beans to tubers. Various types of tubers are easy to find because they are suitable for Indonesia's tropical climate. One of the commonly used tubers is purple yam. Purple sweet potato is an agricultural product and is a traditional food that contains high levels of anthocyanins that function as antioxidants. Purple sweet potatoes which are usually only steamed, fried, boiled and now have the latest innovation by wrapping them using spring roll skins. In addition, sweet potatoes, which are usually processed in large sizes, now come in a mini size that can make it easier for customers to take them anywhere. The purpose of this research is to be traded in the market, because this is a delicious and cheap snack, and of course liked by the public. This research method uses experiments, namely to evaluate the effectiveness of various strategies in purple yam-based entrepreneurial practices. The study involved a series of experiments designed to test various variables, such as production techniques, marketing strategies, and product innovation. Research Results This experimental method aims to develop and evaluate the potential of entrepreneurial businesses based on purple sweet potato processed products. The experiment was carried out through several stages, including identifying the potential of purple yams, developing products, analyzing the market, implementing marketing strategies, and financial analysis. Purple sweet potatoes are chosen because of their high nutritional content and attractive natural color, which can be a plus in product marketing. This study concludes that purple yam-based entrepreneurship has bright prospects and can become a sustainable business model with continuous product innovation creatively.